BASLAWÍSH KLASS OQÍW SABAQLARÍNDA TEKST DÚZIWGE ÚYRETIW METODIKASÍ - Arepbaeva, S.U. (SCIENCE and SOCIETY, 2023)
The article deals with increasing the efficiency of primary school students in the development of consistent written speech. It is said about the formation of the skills of correct writing and correct reading in first graders, especially in first graders.